The stone wife [large type] : a Peter Diamond investigation - Lovesey, Peter (Lovesey, Peter. Peter Diamond mystery., 2014)
In a Bath auction house, a large slab of carved stone is up for sale when there's a hold-up attempt by three masked robbers. They kill the highest bidder, a professor who has recognized the figure carved in the stone as Chaucer's Wife of Bath, and then flee, leaving the stone behind. Peter Diamond and his team are assigned to investigate, and the stone is moved into Diamond's office so he can research its origins. The carving causes such difficulties that he starts to think it has jinxed him. Meanwhile, as Diamond's leads take him to Chaucer's house in Somerset, his intrepid colleague Ingeborg goes undercover to try to track down the source of the handgun used in the murder.